1999
DOI: 10.1097/00004647-199906000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Hemodynamics and Ischemic Tolerance: Lipopolysaccharide-Induced Resistance to Focal Cerebral Ischemia is not Due to Changes in Severity of the Initial Ischemic Insult, but is Associated with Preservation of Microvascular Perfusion

Abstract: Lipopolysaccharide (LPS), administered 72 hours before middle cerebral artery (MCA) occlusion, confers significant protection against ischemic injury. For example, in the present study, LPS (0.9 mg/kg intravenously) induced a 31% reduction in infarct volume (compared with saline control) assessed 24 hours after permanent MCA occlusion. To determine whether LPS induces true tolerance to ischemia, or merely attenuates initial ischemic severity by augmenting collateral blood flow, local CBF was measured autoradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 37 publications
6
70
2
Order By: Relevance
“…Previous quantitative perfusion studies had either examined acute occlusion intervals during which no effect is evident (Chen et al, 1996;Dawson et al, 1999), or had involved hydrogen clearance measurements at one point within the MCA territory (Matsushima and Hakim, 1995;Matsushima et al, 1996). A laser Doppler evaluation in the SHR had been interpreted to exclude perfusion effects (Barone et al, 1998), although a trend toward increased relative flow could be detected during the 2-h interval evaluated.…”
Section: Perfusion Changes and Ischemic Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous quantitative perfusion studies had either examined acute occlusion intervals during which no effect is evident (Chen et al, 1996;Dawson et al, 1999), or had involved hydrogen clearance measurements at one point within the MCA territory (Matsushima and Hakim, 1995;Matsushima et al, 1996). A laser Doppler evaluation in the SHR had been interpreted to exclude perfusion effects (Barone et al, 1998), although a trend toward increased relative flow could be detected during the 2-h interval evaluated.…”
Section: Perfusion Changes and Ischemic Preconditioningmentioning
confidence: 99%
“…In the context of focal ischemia, infarct volumes are reduced by prior global (Simon et al, 1993) or focal ischemia (Barone et al, 1998;Chen et al, 1996;Matsushima and Hakim, 1995), by inflammatory signaling molecules such as lipopolysaccharide (LPS) (Tasaki et al, 1997), by spreading depression (Matsushima et al, 1996;Otori et al, 2003), or even by remote cortical injury that does not induce spreading depression (Muramatsu et al, 2004). A role of perfusion changes in PC has been largely discounted, based on numerous studies that failed to identify cerebral blood flow (CBF) differences between naïve and preconditioned animals during acute intervals after subsequent occlusion, using autoradiographic (Alkayed et al, 2002;Chen et al, 1996;Dawson et al, 1999), hydrogen clearance (Matsushima and Hakim, 1995;Matsushima et al, 1996) or laser Doppler measurements (Barone et al, 1998). Recent results indicate that basal CBF might even be reduced in a preconditioned hemisphere, perhaps secondary to decreases in metabolic rate after treatments that produce cortical injury (Muramatsu et al, 2004;Otori et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance to experimental brain ischemia can be induced by a variety of stimuli that elicit a stress response, such as transient cerebral ischemia (Barone et al 1998), cytokines (Beltrami et al 2003) and endotoxin (Jiang et al 2007). Recent evidence indicates that Toll-like receptors (TLRs) are involved in the preconditioning-induced tolerance to ischemia Puisieux et al 2000;Dawson et al 1999;Tasaki et al 1997;Stevens et al 2008). Toll-like receptors (TLRs) are a family of signal transduction molecules that play a critical role in the induction of innate and adaptive immunity (Medzhitov et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are a family of signal transduction molecules that play a critical role in the induction of innate and adaptive immunity (Medzhitov et al 1997). Preconditioning with TLR4 Puisieux et al 2000;Dawson et al 1999;Tasaki et al 1997) and TLR9 (Stevens et al 2008) ligands has been reported to induce neuroprotection against ischemic injury. By way of example, the TLR4 ligand, lipopolysaccharide (LPS), can induce protection against ischemia-induced brain injury Puisieux et al 2000;Dawson et al 1999;Tasaki et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Dawson et al used autoradiography to show that 15 minutes after the onset of MCAO, CBF was unchanged in animals subjected to lipopolysaccharide preconditioning; however, 4 and 24 hours later, microvascular perfusion as assessed by an intravascular fluorescent tracer technique was preserved at higher levels in preconditioned animals compared with controls. 38 Gustavsson et al observed an attenuation of the CBF decrease during a hypoxic/ischemic injury 24 hours after hypoxic preconditioning, along with an increase in microvascular density, 9 albeit in a neonatal model where angiogenesis is likely to remain more plastic compared with the adult brain. In our model, no increase in vascularization was observed in ischemia-tolerant brains, however, the lower ECP and reduced COX expression pattern suggested a significant decrease in mitochondrial phosphorylation capacity at the rate necessary to meet the cellular energy demand subsequent to NPA administration.…”
Section: Discussionmentioning
confidence: 99%